METHODOLOGICAL PRINCIPLES OF THE DEVELOPMENT OF THE SYSTEM OF ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES - DERGALIUK, Bogdan; KOZHEMYACHENKO, Оlga (Herald of Khmelnytskyi National University. Economic sciences, 2023)
It is justified that the security of the enterprise should be considered from the position of the state of security, which is manifested in the possibility of the development of the enterprise, taking into account the existing resource base. The system of economic security should not contradict the general concept and strategic vector of development of the economic entity, while having appropriate elements that are integral and structured among themselves in the form of appropriate relations. The functions of the economic security system are singled out: monitoring the state of the enterprise's functioning environment for the presence of threats and dangers; preparatory function; an analytical function that allows you to evaluate the received information; the development of preventive measures, which in a certain period of time make it possible to adjust them to ensure the final goal; competitive intelligence, which is the analysis of competitors' activities to identify strengths and weaknesses for further adjustment of the company's development strategy. Based on the functions and tasks, the development of the economic security system of the enterprise must comply with the specified principles, which are the conditions and rules for achieving the set goal. The main principles of the development of the system of economic security of industrial enterprises include the following principles: conformity, integration, continuity, flexibility, complexity, rationality, purposefulness, expediency, adaptability. The organizational support of the system of economic security of an industrial enterprise is proposed, which involves a sequence of three stages. Firstly, the definition of the characteristics of the industrial sector of the enterprise, secondly, ensuring the effective neutralization of threats to the economic security of the industrial enterprise due to the development of a set of measures to ensure economic security and recommendations for their implementation in the practical activities of the enterprise in modern conditions; thirdly, operational management of the system of economic security of the industrial enterprise, taking into account the influence of environmental factors and the adaptive capacity of the enterprise.
Keywords: economic security; industrial enterprises; system of economic security; principles and functions of the system of economic security of the enterprise